Socio Juridical Review Of Effectiveness Fulfillment Of Passengers Security And Safety Rights In Feeder Bus Services (Study At The Pakuan Regional Public Transportation Company, Bogor City) - Garnes Revina Cahya; Saharuddin Daming; M. Mova Al Afghani (JURNAL MAHASISWA YUSTISI, 2026)
The issue of passengers' security and safety rights when using public transportation has recently become an important matter to study considering the many cases of disturbances to passenger security and safety ranging from harassment, theft to accidents involving public transportation. Safety and security are rights that must be given to passengers, as well as the responsibility of transport companies as mandated in the provisions of article 141 paragraph (1) of the Road Transport Traffic Law. The aim of this research is to determine the effectiveness of fulfilling security and safety rights carried out by the Pakuan Regional Public Transportation Company, especially in the Feeder Bus Service and to analyze things that are supporting and inhibiting factors in fulfilling passengers' security and safety rights. This research uses qualitative methods with empirical juridical research and a socio-legal approach. The results of the research show that the Pakuan Regional Public Transportation Company has fulfilled its obligations to protect the security and safety rights of passengers. Apart from that, based on the survey results it can be seen that the fulfillment of passengers' security and safety rights is running effectively. However, supervision and evaluation are still needed to improve the services provided.